The Effectiveness of Peer Educator-Based Education as A Model for Handling Online Game Addiction in Adolescents During the Covid-19 Pandemic - Puji Lestari; Liyanovitasari Liyanovitasari (Indonesian Journal of Global Health Research, 2021)
The Covid-19 pandemic has limited all community activities to leaving the house. This has taken a lot of time for teenagers to use smartphones which has triggered addiction to online games. Increased addiction to online games harms adolescents, including teenagers who become lazy in their activities, are often alone, lack socializing, and become introverted individuals. The adolescent period is a period that is very close to peer groups, requires recognition from groups or peers, and requires a new identity that can increase self-esteem. The purpose of this study was to determine the effectiveness of peer educator-based education as a model for dealing with online game addiction in adolescents. This study employed a quantitative approach. The research design was a quasi-experimental or pre-experimental design with the type of one-group pretest-postest design. The research respondents were 107 students with the criteria who play online games, used purposive sampling. This study provided video interventions through WhatsApp group media and measuring behavior data using google forms. The instrument used to measure online game addiction behavior was the Game Addiction Scale (GAS)for adolescents developed by Lemmens in 2009. Data analysis used the Wilcoxon test to determine differences in adolescent behavior before and after peer educators were educated about handling online game addiction. The results showed that the behavior of adolescents before treatment was in the online game addiction category 55,1% and it decreased to 11.2% after treatment. There were differences in the behavior of adolescents before and after education by peer educators with each p-value of 0.000.